Implementation of a DVB-T2 passive coherent locator demonstrator - Malape, Micheal Thatohatsi (Department of Electrical Engineering, 2020)
Passive Coherent Locator (PCL) radar’s have seen extensive research in the past decade. PCL radars utilize illuminators of opportunity (IOO) as transmitters to perform target detection. Particular interests in FM (analogue) and DVB-T/T2, DAB (digital) radio frequency signals has seen significant focus as possible illuminators for radar processing. The University of Cape Town (UCT) , in particular, has extensive history on passive radar research including the implementation of a full narrowband FM PCL radar demonstrator. This dissertation details the design and implementation of a DVB-T2 Passive Coherent Locator radar demonstrator isolating a single DVB-T2 channel. This includes the design, construction, testing and evaluation of the full PCL radar system. System planning was implemented detailing the possible IOOs available in the Cape Town area. This was followed by signal propagation simulations to determine the effects the environment would have on the transmitted wave utilising Advanced Refractive Effects Prediction System (AREPS) model. A front-end design was simulated and implemented utilizing commercial-of-the-shelf (COTS) hardware including the National Instruments Ettus N210 software defined Radio (SDR) based on the system planning results. A processing chain for DVB-T2 based PCL radar was then investigated to determine the most optimal processing chain structure, with the mismatched filtering technique being proposed as an ideal choice for DVB-T2 PCL radar. The proposed processing chain was implemented and tested on both the Ettus N210 front-end as well as a commercial system. The full radar demonstrator was then tested by observing the air traffic surrounding the Cape Town International airport resulting in successful detections of aircraft in the surveyed environment.